Relaciones en la Escuela: Una propuesta para promover prácticas propicias para la educación (2013)
ABSTRACT This report aims to make the approach from educational psychology to the different needs identified in the population, the College Diocesaño Monseñor Baltasar Álvarez Restrepo. This developed three areas of focus: the first relates to life together, especially in primary groups, the second, is approach the recognition and establishment of learning strategies for students with academic difficulties and finally we will go forward with Career Couseling process in grades 10° and 11°.